Brodalumab: a promising option in the management of psoriasis - Sahay, Melina Infenta; Ravindranath, Roshini; Krishnamoorthy, Snehalatha; Sriram, Damal Kandadai; George, Melvin (International Journal of Basic & Clinical Pharmacology, 2020)
Brodalumab, a human monoclonal antibody approved as a biological therapy for treating psoriasis. Due to its consistent results across several clinical studies in treating patients with plaque psoriasis, in 2016 it was first approved worldwide in Japan followed by US FDA approval in 2017 and the European medicines agency. Brodalumab, selectively binds with higher affinity to IL-17RA, thereby blocking the actions of IL-17A, E and F. This act as a novel mechanism to inhibit the inflammation, hyperproliferation, skin thickening and other clinical symptoms associated with psoriasis. The safety and adverse effects of Brodalumab were similar to other IL-17 inhibitors, frequently reported adverse events were nasopharyngitis, neutropenia, and candidiasis. The FDA has recommended a boxed warning for the suicidal tendencies that could occur among Brodalumab users. This review is an endeavor to depict the drug’s mode of action, pharmacokinetics, safety, and efficacy as well as its current status among other drugs targeting IL-17.